Comparing delayed cord clamping and umbilical cord milking during elective cesarean section for the neonatal outcome - Tamer A. Hosny; Amal Z. Azzam; Mohga Ashraf Said; Bahaa Salah Hammad (Elsevier, 2023)
Objectives: to compare between immediate cord clamping, delayed cord clamping, and umbilical cord milking and their effects on hemoglobin and bilirubin level in term infants in cesarean section. Study design: A randomized clinical trial was conducted from November 2021 to June 2022, including 162 full term pregnant women undergoing elective cesarean section at EL-Shatby Maternity University Hospital. They were randomly assigned (1:1:1 ratio) either to immediate cord clamping just after delivery (Group 1) or delayed cord clamping for 30 s (Group 2) or umbilical cord milking 10 times for 10-15 s (Group 3). The primary outcome measures included hemoglobin and hematocrit levels of the newborn at birth and the secondary outcome was bilirubin level measurement at 72 h of life. Results: one hundred sixty- two newborns were randomized into 3 groups, fifty-four cases in each, and were investigated on hemoglobin and hematocrit levels; five were lost to follow-up and one hundred fifty-seven were tested for bilirubin. Participants among groups had no significant difference regarding demographic and clinical characteristics, regarding the hemoglobin at birth it was significant higher in the umbilical cord milking group (Group 3) through all groups (14.91 ± 0.91 g/dl vs15.38 ± 0.74 g/dl vs 16.56 ± 1.03 g/dl, p value <0.001), regarding hematocrit level at birth it was significant in the umbilical cord milking group (Group 3) through all groups (44.71 ± 2.94 vs 46.48 ± 2.61 vs 49.74 ± 3.26, p value <0.001). On the other hand, bilirubin level after 72 h had no significant different through the 3 groups (8.80(IQR 4.50-17.20), vs 9.70(IQR3.50-14.70), vs 8.50(IQR 3.20-19.50), respectively p value= 0.348) Conclusion: this study showed that umbilical cord milking 10 times for 10-15 s is more effective than delayed cord clamping for 30 s in enhancing hemoglobin and hematocrit levels in newborn delivered by cesarean section with no significant difference on bilirubin level in the newborn.